The cooking task: making a meal of executive functions - Doherty, T. A.; Barker, L. A.; Denniss, R.; Jalil, A.; Beer, M. D. (Frontiers in Behavioral Neuroscience, 2015)
Current standardised neuropsychological tests may fail to accurately capture real-world executive deficits. We developed a computer-based Cooking Task assessment of executive functions and trialled the measure with a normative group before use with a head-injured population. Forty six participants completed the computerised Cooking Task and subtests from standardised neuropsychological tasks, including the Tower and Sorting Tests of executive function from the D-KEFS, and the CAMPROMPT measure of prospective memory, in order to examine whether standardised executive function tasks, predicted performance on measurement indices from the Cooking Task. Findings showed that verbal comprehension, rule detection and prospective memory contributed to measures of prospective planning accuracy and strategy implementation of the Cooking Task. Results also showed that functions necessary for cooking efficacy differ as an effect of task demands (difficulty levels). Performance on rule detection, strategy implementation and flexible thinking EF measures contributed to accuracy on the Cooking Task Findings raise questions about the functions captured by present standardised tasks particularly at varying levels of difficulty and during dual-task performance. Our preliminary findings also indicate that Cooking Task measures can effectively distinguish between EF and FSIQ abilities. Results of the present study indicate that the Cooking Task shows promise as an ecologically valid measure of executive function for future use with a head-injured population and indexes selective EF’s captured by standardised tests.